IMPROVE LISTENING ABILITY THROUGH DICTATION TECHNIQUE IN DESCRIPTIVE TEXT AT SMK HKBP PEMATANGSIANTAR - Sitanggang, Anita; Panjaitan, Anne Silvia; Sinaga, Ita Christine; Siburian, Ruth Junisa (Transpublika Publisher, 2022)
This research aims to improve listening ability students of English subjects using the dictation method and find the effectiveness of the dictation method in an effort to improve ability listening to students on descriptive text of class X IA 1 students of SMK HKBP PEMATANGSIANTAR. This research is a classroom action research conducted in the first semester of the year 2021/2022 teaching. The subjects of this research were students of class X IA 1 SMK HKBP PEMATANGSIANTAR. The object of this research is the improvement of listening ability English lessons on descriptive text with the dictation method. Classroom action research it covers 2 cycles. Each cycle consists of four stages, namely: (1) planning, (2) action, (3) observation, and (4) reflection. The findings from classroom action research are (1) Students' listening ability increase with the use of the dictation method, (2) The average score of students in the pre-cycle action is 56.84% including the